Sírio-libanês, sabores e práticas de cozinhar: memórias, gênero, práticas e apropriações (São Paulo, séculos XX e XXI) - Abdala, Alfredo Ricardo (2022)
This thesis aims at understanding how food considered Arab is/was recognized and appropriated in the city of São Paulo, being present in homes, catering establishments, deliveries, fast foods, being associated with homemade food, quick snacks and even upscale restaurant dining experiences. Knowing that the knowledge and practices related to cooking and food are female attributions in the Syrian-Lebanese community, and that they were generationally transmitted among women, the investigation incorporates a gender perspective, demarcating the experiences, roles and family relationships experienced in the society of origin and transferred to the colony established in São Paulo. To this end, ethnographic research was carried out in catering establishments, homes, institutions and NGOs linked to displacements and the already established SyrianLebanese colony. Adding oral history as a methodology, testimonies from immigrants and their descendants were collected, there was also the collection of photographs, menus and recipes, in an attempt to recompose the experiences of work in the kitchen, recipes and practices, the transmission of this knowledge, the forms of consumption and sociability that involved food. Initially, the thesis looks at the occupations of Syrian and Lebanese immigrants, where they established residences, places of work and leisure, highlighting the search for integration with the people of São Paulo and the propagation of their culture, including food, tastes, flavors and cooking practices. It is observed the transposition of gender roles and behaviors, marriage policies, family organization and transmission of traditions, highlighting the role of women, also documenting the female pioneer in the enterprise of catering establishments. The investigation focuses on the analysis of the knowledge and cooking practices of immigrants, tracking their transformations over time, documenting a trajectory that started from an artisanal kitchen and assumed new forms of production (techniques, instruments, technologies, times and rhythms were transformed) and commensality practices. Finally, professional establishments and their practices and appropriations of what is considered "Arab cuisine" were researched, considering the spread of fast foods and food trucks and the spread of consumption of their products, in particular esfihas and kibes